A class of two-stage distributionally robust games - Li, Bin; Sun, Jie; Xu, Honglei; Zhang, Min (AMER INST MATHEMATICAL SCIENCES-AIMS, 2017)
An N-person noncooperative game under uncertainty is analyzed, in which each player solves a two-stage distributionally robust optimization problem that depends on a random vector as well as on other players' decisions. Particularly, a special case is considered, where the players' optimization problems are linear at both stages, and it is shown that the Nash equilibrium of this game can be obtained by solving a conic linear variational inequality problem.